By hook & ladder : the story of fire fighting in America - Loeper, John J. (New York : Atheneum, 1981)
A history of fire fighting including information on firemen, female firefighters, fire engines, fire fighting techniques, and some famous fires in American history.
Includes bibliographical references: p. [77]
Keywords: Fire extinction -- Juvenile literature; Fire fighters -- Juvenile literature; Fire extinction; Fire fighters